Health Beliefs on the Behavioral Adoption of Mammography Screening Moderated by Knowledge and Marital Status: A Path Analytic Model - Moey, Soo Foon; Che Mohamed, Norfariha; Lim, Bee Chiu (Malaysian Public Health Physicians' Association, 2021)
Despite the effectiveness of mammography for early breast cancer detection, its’ utilization among Malaysian women remains low. Health beliefs are closely related to health screening behavior. Hence, it is important that health beliefs are employed when exploring mammography screening behavior. Thus, the study utilized HBM constructs in predicting the variance in adoptive behavior of mammography. A multi-stage, stratified random sampling method was utilized to select the polyclinics in Kuantan, Pahang. Using sample size calculation at 5% type 1 error, p < 0.05 and absolute error at 2%, 520 Malaysian women aged 35 to 70 years were randomly selected. Sets of copyrighted, validated questionnaire were used to obtain the data. Structural equation modeling using Mplus was used to test the model. All health beliefs were found to significantly influence the behavioral adoption of mammography screening. Socio-demographic factors (married women) were found to moderate significantly the relationship between perceived susceptibility and behavioral adoption of mammography. Further, knowledge and married women were found to significantly affect selfefficacy. Additionally, perceived severity, motivator factors and perceived benefits were found to significantly influence self-efficacy and that self-efficacy significantly influences the behavioral adoption of mammography screening. However, a negative correlation was found between perceived severity and perceived barriers on the behavioral adoption of mammography. The model can be used as an interventional tool in designing promotional and educational programs to encourage women to adopt mammography screening.